Analysis of the neutron noise induced by fuel assembly vibrations. (May 2021) - Zoia, Andrea; Rouchon, Amélie; Gasse, Baptiste; Demazière, Christophe; Vinai, Paolo
Highlights: We investigate some aspects of the neutron noise equations in the Fourier domain. We consider periodic fuel rod vibrations, with focus on the double frequency effect. We do not truncate the noise source at the first order and do not resort to linearization. Abstract: The investigation of neutron noise is key to several applications in nuclear reactor physics, such as the detection of control rod or assembly vibrations and the diagnostic of coolant speed and void fraction. In this paper we will elucidate some aspects of the noise equations in the Fourier domain, for the case of periodic fuel rod vibrations with frequency ω 0 in a small symmetrical system in which the perturbation is centrally located. We will in particular focus on the double frequency effect, i.e., the emergence of a noise component at 2 ω 0 (possibly stronger than the one at the fundamental frequency ω 0 ). Our analysis will be carried out without truncating the noise source at the first order and in the context of a non-perturbative approach (i.e., without resorting to linearization). For this purpose, we will select a simple benchmark configuration that is amenable to accurate reference solutions obtained by solving the exact time-dependent transport equations. The analysis carried out in this work suggests that the non-perturbative noise equations are mandatory in order to properly discriminate the possible emergence of double frequency effects in neutron noise, especially in view of comparing simulation results to experimental data.